2012
DOI: 10.1088/0031-9155/57/4/983
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Gaussians: a study of single-spot modeling for scanning proton dose calculation

Abstract: Active spot scanning proton therapy is becoming increasingly adopted by proton therapy centers worldwide. Unlike passive-scattering proton therapy, active spot scanning proton therapy, especially intensity-modulated proton therapy, requires proper modeling of each scanning spot to ensure accurate computation of the total dose distribution contributed from a large number of spots. During commissioning of the spot scanning gantry at the Proton Therapy Center in Houston, it was observed that the long-range scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 27 publications
4
85
2
Order By: Relevance
“…In fact, we have recently demonstrated that a modified Cauchy-Lorentz distribution function is a better choice for modeling the low-dose envelopes in the water phantom. 25 Between March 2010 and June 2012, we treated more than 500 patients with scanning proton beams using the DG fluence model, including approximately more than 150 patients with central nerve system, head and neck, and other cancers. We used SFUD, single field integrated boost, and IMPT for these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we have recently demonstrated that a modified Cauchy-Lorentz distribution function is a better choice for modeling the low-dose envelopes in the water phantom. 25 Between March 2010 and June 2012, we treated more than 500 patients with scanning proton beams using the DG fluence model, including approximately more than 150 patients with central nerve system, head and neck, and other cancers. We used SFUD, single field integrated boost, and IMPT for these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these results, in addition to the well known double Gaussian and to the more recently proposed and accurate parametrizations (triple Gaussian [11] and double Gaussian CauchyeLorentz [13]), the GausseRutherford function is a good compromise to evaluate the lateral energy deposition of real beam shapes: indeed, with only 4 free parameters, it ensures a good accuracy, but also a fast calculation time. Moreover, this parametrization is firmly justified by a physical explanation because the tails of the distribution are also due to the single scattering events at big angles, as shown by Rutherford.…”
Section: Resultsmentioning
confidence: 98%
“…Among these it is worth mentioning the approach of Soukup et al [12] that parametrizes the nuclear halo tails with a modified CauchyeLorentz function, the work of Li et al [13] and the recent review by Gottschalk [14] that proposes a very detailed model with 25 parameters.…”
Section: Review Of Multiple Scattering Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The beam spread is described by the parameter sigma 1 (σ), the Gaussian approximation of the main part of the dose distribution in a single spot (20). The results are presented below in terms of σ.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%